The New Humanities Project—Reports from Interdisciplinarity - Mauro Bergonzi; Francesco Fiorentino; Domenico Fiormonte; Laura Fortini; Ugo Fracassa; Michele Lucantoni; Massimo Marraffa; Teresa Numerico (Humanities, 2014)
New Humanities is an international research and teaching project promoted by an interdisciplinary group of people from five different faculties and departments based at the University of Roma Tre. Initially set up as a forum for academic dialogue between the humanities and the sciences (including social sciences), the project became a transition space and platform for experiencing new research methodologies and teaching curricula that would question the present epistemological order of the European university system. In order to develop this approach, we have organized our work around a number of interdisciplinary clusters, each describing an epistemological node. In this paper we will discuss five interconnected case studies that emerged from an active collaboration between scientists and humanists. The first node, Protocols of Vision, investigates the cognitive nature of sensory perception and the different forms of knowledge it produces—empirical, artistic, and scientific. Memory: Mathematics, Computer Science, and Literature recapitulates many of the different threads in these discussions by exploring the interdependencies between the various kinds of memory: from external to subjective memory, from storage tools and techniques of self-construction to the invariance of mathematical structures. The third node, Signs and Bodies between Digital and Gendering, reflects on the problematic relationship between digital media and literary and linguistic gendering. Narrative Identity: Nature, Ontogeny and Psychopathology critically re-examines the main concepts and theories concerning the nature, ontogeny, and pathologies of the autobiographical self or narrative identity. Finally, the last node, Contribution of Quantum Physics to the Idea of Consciousness is a cross-cultural investigation into the phenomenon of consciousness tackled from the points of view of quantum field theory and ancient Indian philosophy.